Система контроля выбросов токсичных газов на теплоэлектростанции - Maksimenko, Y. N.; Tsvelych, Y. M. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
An analysis of the requirements for monitoring systems of toxic gas emissions from boiler units of thermal power plants is presented. The composition of a three-level system developed for the Trypilska Thermal Power Plant is described. The main technical solutions and the selection of elements included in this system are analyzed.